1983
DOI: 10.1007/bf01971131
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine reduces the size of cells in prolactin-secreting pituitary adenomas

Abstract: The morphometric analysis of the size of adenomatous prolactin cells shows that bromocriptine-induced cell shrinkage halts if treatment with the drug is discontinued for more than 2 days. Different cell components (nucleus, cytoplasm, nucleolus) do not react to treatment to the same extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…A further ef fect of bromocriptine was the virtual elimination of cells with electron-dense cytoplasm and greatly dilated ER ('dark' cells) which were a prominent feature during es trogen withdrawal. Bromocriptine-induced loss of ER has been described in prolactin cells [26,27], but the re duction in numbers of 'dark' cells after 2 h exposure to bromocriptine is difficult to explain. The role of these cells is unknown [28].…”
Section: Discussionmentioning
confidence: 99%
“…A further ef fect of bromocriptine was the virtual elimination of cells with electron-dense cytoplasm and greatly dilated ER ('dark' cells) which were a prominent feature during es trogen withdrawal. Bromocriptine-induced loss of ER has been described in prolactin cells [26,27], but the re duction in numbers of 'dark' cells after 2 h exposure to bromocriptine is difficult to explain. The role of these cells is unknown [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment with DA causes late inhibition of prolactin gene transcription, and the resulting decrease in hormone synthesis causes further drop of PRL levels [40][41][42]. Additionally, DA promotes tumor regression due to lactotroph cell size reduction [43], and to degenerative and necrotic changes in tumor cells [44,45]. The lactotroph cell size reduction is caused by a decrease in cytoplasmic organelles [45][46][47][48][49], with concomitant increase in perivascular fibrous tissue [50], and these changes are reversible once the treatment with the drug is discontinued [51].…”
Section: Discussionmentioning
confidence: 99%
“…Prolactinomas can be primarily managed by medical therapy, but the mechanism by which the dopamine agonists (DA) have their tumour shrinkage effect is unclear. A number of reports have suggested that tumour regression was due to lactotroph cell size reduction [3][4][5], and subsequent ultrastructural studies have demonstrated a rapid involution of rough endoplasmic reticulum and Golgi apparatus, reversible after drug withdrawal [6].…”
Section: Introductionmentioning
confidence: 99%